2010
DOI: 10.1111/j.1462-2920.2010.02371.x
|View full text |Cite
|
Sign up to set email alerts
|

Epibacterial community patterns on marine macroalgae are host‐specific but temporally variable

Abstract: Marine macroalgae are constantly exposed to epibacterial colonizers. The epiphytic bacterial patterns and their temporal and spatial variability on host algae are poorly understood. To investigate the interaction between marine macroalgae and epiphytic bacteria, this study tested if the composition of epibacterial communities on different macroalgae was specific and persisted under varying biotic and abiotic environmental conditions over a 2-year observation time frame. Epibacterial communities on the co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

27
255
2
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 273 publications
(305 citation statements)
references
References 63 publications
(70 reference statements)
27
255
2
1
Order By: Relevance
“…It classifies as a member of the genus Granulosicoccus (Lee et al, 2007). Related sequences have been detected on the red seaweed Delisea pulchra, the green seaweed U. australis (Longford et al, 2007), the brown seaweed Fucus vesiculosus (Lachnit et al, 2010) and on the kelp (brown seaweed) Saccharina latissima (Staufenberger et al, 2008), suggesting that organisms within this genus share a preference for seaweeds. The alphaproteobacterial OTU 90 is less abundant (maximum 7.65%), yet frequently detected on L. hyperborea (Table 1, Figure 4a).…”
Section: Community Composition and Proposed Functions Of Abundant Otusmentioning
confidence: 99%
“…It classifies as a member of the genus Granulosicoccus (Lee et al, 2007). Related sequences have been detected on the red seaweed Delisea pulchra, the green seaweed U. australis (Longford et al, 2007), the brown seaweed Fucus vesiculosus (Lachnit et al, 2010) and on the kelp (brown seaweed) Saccharina latissima (Staufenberger et al, 2008), suggesting that organisms within this genus share a preference for seaweeds. The alphaproteobacterial OTU 90 is less abundant (maximum 7.65%), yet frequently detected on L. hyperborea (Table 1, Figure 4a).…”
Section: Community Composition and Proposed Functions Of Abundant Otusmentioning
confidence: 99%
“…These bacteria have been especially well studied from terrestrial habitats [45,46], but have also been reported from marine habitats. Rhizobiales are common epiphytes of Ulva seaweeds [47][48][49][50] and have also been isolated from the surface of kelps where they display antimicrobial activity [13]. Additionally, a Rhodopseudomonas species with the potential to fix nitrogen was isolated from the rhizoidal cytoplasm of the siphonous green seaweed Caulerpa taxifolia [19].…”
Section: (A) Diversity Of Endogenous Bacteriamentioning
confidence: 99%
“…In some cases, algal species host specific bacterial assemblages across large geographic distances (Lachnit et al, 2009). To date, most studies on algal associated bacterial communities have focused on temperate, fleshy algal species (Lachnit et al, 2011) with the exception of a few studies of tropical fleshy algae (Barott et al, 2011;Sneed and Pohnert, 2011). Although CCA are known to be important settlement substrata for a number of invertebrate species and bacteria are known to produce chemical cues that induce invertebrate larval settlement, little is known about the bacterial communities associated with CCA.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have demonstrated that different species of macroalgae harbor unique bacterial communities (Longford et al, 2007;Lachnit et al, 2009Lachnit et al, , 2011Sneed and Pohnert, 2011). Within a given geographical area, bacterial communities are often more similar on individuals from the same algal species than they are to individuals from other algal species (Sneed and Pohnert, 2011).…”
Section: Introductionmentioning
confidence: 99%